The Preadult Origins of Postmaterialism: A Longitudinal Sibling Study - Martin Kroh (European Journal of Political Research, 2009)
Using a research design that traces siblings' preferences for postmaterialist values in Germany over two decades, this article provides new evidence on the origins of value preferences. Focusing on Inglehart's thesis of value change, the combined socialisation and scarcity hypothesis is tested against the social learning hypothesis – a prominent rival account of preadult value preference formation. Sibling estimates show that the shared preadult environment does indeed exert lasting effects on preferences for postmaterialist policies. In addition to the weak effect of the shared experience of socioeconomic scarcity, it is found that the intergenerational transmission of postmaterialism, disregarded by Inglehart's original thesis, plays a significant role in value preference acquisition. The implications of individual-level findings for forecasts of aggregate-level trends in value change are discussed.
Additional information: The definitive version is available at http://www.wileyonlinelibrary.com/journal/ejpr or http://dx.doi.org/10.1111/j.1475-6765.2009.00843.x
Keywords: Z13; D72; C23; C25; 330; Familie; Ethik; Panel; Deutschland